Citocinas plasmáticas como biomarcadores de morbidade cardíaca na doença de Chagas - Giovane Rodrigo de Sousa (2013)
The present study was designed to determine if the expression of immunological markers in patients with different forms of Chagas disease is associated with determining factors of cardiac morbidity in this disease. Patients infected with Trypanosoma cruzi were grouped as indeterminate form (IND) and cardiac (CARD) patients ranging from 23 to 69 years of age (mean of 45.6 ± 11.25). The IND group included 82 asymptomatic individuals, ranging from 24 to 66 years of age (mean of 39.6 ± 10.3), with no significant alterations in electrocardiography, chest X-ray, and echocardiogram. The CARD group included 94 patients ranging from 23 to 69 years of age (mean of 48 ± 12.52) presenting with dilated cardiomyopathy, characterized by the echocardiographic finding of a dilated left ventricle with impaired ventricular systolic function. Healthy individuals, ranging from 29 to 55 years of age (mean of 42.6 ± 8.8), from a non-endemic area for Chagas disease and showing negative serological tests for the infection were included as a control group (NI). Data analysis demonstrated that IND patients have a higher intensity of interleukin (IL)-10 expression when compared with individuals in the other groups. By contrast, the forms of inflammatory cytokine expression, such as interferon (IFN)-, tumor necrosis factor (TNF)-, IL-6, and IL-1, proved to be the highest in the CARD group. Correlated analysis showed that high IL-10 expression was associated with better cardiac function, as determined by left ventricular ejection fraction and left ventricular diastolic diameter values. The findings support the protective role of IL-10 against cardiac damage in human Chagas disease. Altogether, the results indicate that a fine balance between regulatory and inflammatory cytokines represents a key element in the establishment of distinct forms of chronic Chagas disease. Furthermore, this study helped to shed light on the complex cytokine network underlying the immunopathogenesis of chronic chagasic cardiopathy.